KARAKTERISTIK PETANI DAN INPUT USAHATANI DI SENTRA PRODUKSI KENTANG JAWA BARAT: STUDI KOMPARASI ANTARA KABUPATEN BANDUNG DAN KABUPATEN GARUT - Rasmikayati, Elly; Karyani, Tuti; Saefudin, Bobby Rachmat (Agros Journal of Agriculture Science, 2024)
This potato production can be personally profitable for farmers, with high demand farmers can have high profits by carrying out potato production and becoming a supplier of potato supplies. However, there is a decrease in harvested area in West Java Province, this indicates that there are problems in technical and agricultural input in potato farming in West Java Province. The aim of this research is to compare farmer characteristics and potato farming inputs between Bandung and Garut Regencies. The research method used is descriptive statistics using parametric statistical testing tools and crosstabs. The population in this study were potato farmers in Bandung and Garut Regencies with respondents respectively 382 Potato Farmers in Bandung Regency and 118 Potato Farmers in Garut Regency, with the selection of respondents using a two-stage stratified sampling technique. The results of the research show that the majority of potato farmers in Bandung have elementary school education, new experience, young age, high capital, medium land, seeds ≤0.5 kg, labor 1001 – 1500 hok, fertilizer ≤ 2 kg, pesticide <0.05 liters, and other costs <0.5 million. Meanwhile, in Garut the level of education is elementary school, experience, old age, moderate capital, land ≥ 2.0 ha, seeds > 1.5 kg. labor >1500 hok, fertilizer >6.0 kg, pesticide 0.05 – 0.1 liter, and other costs 1.0 – 1.99 million. Then, there are real differences in farmer characteristics and potato farming inputs between Bandung and Garut Regencies. Key-words: comparative study, farmer characteristics, farming inputs, potatoes.